The Morphology Characteristics of Plant Gambir (Uncaria gambire Roxb.) in Pakpak Barat District - Sebayang, Lukas; Afni Hardyani, Mieke (Talenta Publisher, 2020)
Gambier (Uncaria gambire Roxb) is plantation sector sub commodity which was generally managed by people traditionally but that gambir is exporting commodity only some of consumed by small of society. Gambier plant type that exist in Pakpak Bharat generally not been known as morphology. It is caused by lack of knowledge of community resources Bharat Pakpak to know specifically the type of plants are planted gambier. For that survey gambir plant morphological characteristics in some areas as the center of the district gambir Pakpak Bharat in May-August, 2017. The purpose of this study was to obtain data and information about the types / varieties of gambier plants cultivated by farmers in Pakpak Bharat Regency. The results obtained from the characteristic aspects of plant morphology there are 4 types / types of plant gambier Pakpak contained in Bharat. 4 types of plant gambier it: (1) Type of reddish leaf , known as